VARIASI MENGAJAR GURU DALAM MENGATASI KEJENUHAN SISWA PADA MATA PELAJARAN BAHASA ARAB DI MTS AL WASHLIYAH TANJUNG BERINGIN - Dara Davani; Ellisa Fitri Tanjung (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Variation is a skill that teachers need to master in delivering learning to overcome boredom among students. Variation in learning is a change in the activity process which aims to increase students' learning motivation and reduce boredom. Teachers as part of the educational system framework are required to always develop teaching skills in accordance with the times and the environment in which the educational process is carried out. This research method uses qualitative research. The type of research carried out is field research. The sources of this research are primary and secondary data sourced from Arabic language teachers and students. Data collection uses observation, documentation and interview techniques. This research was conducted at MTs Al Washliyah 31 Jalan Pahlawan Number 02, Pekan Tanjung Beringin Village, Serdang Bedagai Regency.